Presente y perspectivas de las humanidades digitales en América Latina - Víctor Gayol; Jairo Antonio Melo Flórez (Mélanges de la Casa de Velázquez, 2017)
This contribution is a critical review of discussions on Digital Humanities and Digital History in latin America and is potential to become a disciplinary field.